Modelling and forecasting on paddy production in Kelantan under the implementation of system of rice intensification (SRI) - Hiew, Yeap Seng (2011)
The behaviour of the paddy total production and its future production is depending on several important factors such as the water quality, the soil management and also the usage of proper field management system. The introduction of System of Rice Intensification (SRI) that was initiated in India has been brought over into Malaysia several years ago, although it is still not completely implemented, but it did show positive development, especially in land efficiency and production per hectare. The main purpose of this study is to develop a models that not only best describes the behaviour of the paddy total production but also capable to forecast the future paddy production with greater accuracy. The second purpose for this study is to determine the relationship between the implementation of SRI and the acceptance of planters in Kelantan for this cultivation method. Yearly paddy production data for the period of 1970-2009 of Kelantan were analysed by time series methods. Several individual forecasting methods such as Brown's Double Exponential Smoothing, Linear's Double Exponential Smoothing, Winter's Multiplicative Exponential Smoothing, Damped Trend and Random Walk method were used to determine the best forecasting model for the data. The composite methods were calculated and computed under normalize weight method and fit regression weight method to obtain the best composite forecast method for the future paddy production analysis in Kelantan. Autocorrelation and several others measurements were used to determined the model efficiency and validity. The best methods will derives the best fit model for this study in determine the future paddy production, while the implementation of SRI is one of the reasons in contribution of the increases in productivity.